Comparative study between breast conservative surgery and modified radical mastectomy in early stage of breast carcinoma in a tertiary care hospital - Joty, Syeda Mehbuba; Saiyara, Noshin; Shishir, M. Tareq Anwar; Islam, Faridul; Khan, Mahidur Rahman; Sarker, Ashok Kumar; Ahsan, S. M. Mortaza; Nuh, Mohsin Tonoy (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is the most prevalent cancer in women globally, with two million new cases and more than half a million deaths each year. Surgery is the key component of treating breast cancer and there are two primary types of breast surgery available: breast conservative surgery and modified radical mastectomy. The aim of this study was to compare BCS and MRM in the treatment of early-stage breast carcinoma. Methods: This was a prospective observational study that involved 74 patients and was carried out in the Department of Surgery at Shaheed Suhrawardy Medical College & Hospital and Enam Medical College & Hospital with an 18-months minimum follow-up. The time frame for inclusion was from July 2018 through July 2020. There were two patient groups, 37 patients in Group A who underwent breast conservative surgery and Group B was made up of 37 individuals who had MRM for early-stage breast carcinoma. Results: With a mean age of 47.65 years in the BCS group and 48.19 years in the MRM group, the operative time for BCS was 1.04±0.25 hours, whereas 3.20±0.48 hours for MRM. Statistically significant higher amount of post-operative drainage volume in MRM group compared to BCS group (p value=0.000). With an excellent aesthetic outcome rate in BCS group (p value<0.0001) as well as better quality of life than MRM group. Conclusions: Breast conservative surgery and modified radical mastectomy are both oncologically safe treatments for early-stage breast cancer with multidisciplinary approach. BCS offers less trauma, infection and hospital stay; better aesthetic outcome and quality of life than MRM, making it more deserving of being promoted clinically in the treatment of early-stage breast cancer.